Specific mutation screening of TP53 gene by low-density DNA microarray - Angélica Rangel-López (Dove Medical Press, 2009)
Angélica Rangel-López1–3, Alfonso Méndez-Tenorio3, Kenneth L Beattie4, Rogelio Maldonado3, Patricia Mendoza1, Guelaguetza Vázquez1, Carlos Pérez-Plasencia5, Martha Sánchez2, Guillermo Navarro6, Mauricio Salcedo11Laboratorio de Oncología Genómica, Unidad de Investigación Médica en Enfermedades Oncológicas, Hospital de Oncología, CMN Siglo XXI-IMSS, Mexico City, Mexico; 2Unidad de Investigación Médica en Enfermedades Nefrológicas, Hospital de Especialidades, CMN Siglo XXI-IMSS, Mexico City; Mexico; 3Laboratorio de Biotecnología y Bioinformática Genómica, Escuela Nacional de Ciencias Biológicas, IPN Mexico City, Mexico; 4Amerigenics, Inc., Crossville, TN, USA; 5Unidad de Investigación Biomédica en Cáncer, Instituto de Investigaciones Biomédicas, Universidad Nacional Autónoma de México UNAM, Instituto Nacional de Cancerología INCAN, Mexico City, Mexico; 6Laboratorio de Organometálicos UNAM, Mexico City, MexicoAbstract: TP53 is the most commonly mutated gene in human cancers. Approximately 90% of mutations in this gene are localized between domains encoding exons 5 to 8. The aim of this investigation was to examine the ability of the low density DNA microarray with the assistance of double tandem hybridization platform to characterize TP53 mutational hotspots in exons 5, 7, and 8 of the TP53. Nineteen capture probes specific to each potential mutation site were designed to hybridize to specific site. Virtual hybridization was used to predict the stability of hybridization of each capture probe with the target. Thirty-three DNA samples from different sources were analyzed for mutants in these exons. A total of 32 codon substitutions were found by DNA sequencing. 24 of them a showed a perfect correlation with the hybridization pattern system and DNA sequencing analysis of the regions scanned. Although in this work we directed our attention to some of the most representative mutations of the TP503 gene, the results suggest that this microarray system proved to be a rapid, reliable, and effective method for screening all the mutations in TP53 gene.Keywords: oligonucleotide microarray, TP53 gene, point mutations